STRATEGI PENGEMBANGAN OBYEK WISATA BAHARI KABUPATEN NABIRE PROVINSI PAPUA - , Corneeles Anthonius nicolaas, SE, Drs. Ahmad Jamil, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study objective was to formulate a strategy of maritime tourism object development (coral ridge ecosystem) to increase amount of foreign and domestic tourists visiting the Nabire District. This research was done by survey approach using questionnaires with closed end question. Using respondent perception, and scoring/ranking, the researcher did validity test for valid results